Application of Recycle Material in Construction Industry a Method of Sustainable Development - Hegde, Gurumurthy; Namdar, Abdoullah; Ideris, Zakaria (Engineering and Technology Publishing, 2013)
The compressive strength of cement pastes is paly important role in concrete characteristics and structure stability. Many researchers have been involved in enhancing and introducing new composite material. In this research work, it is aimed to use natural minerals present in sawdust powder for improving compressive strength of Ordinary Portland Cement (OPC) pastes. The micro properties, crystalline structural and hydration of OPC paste have been investigated using X-ray diffraction (XRD) and Atomic Force Microscopy (AFM). The results indicated blending of 4% of sawdust powder in OPC paste is improved compressive strength of OPC paste considerably after 28 and 56 days. It has good agreement with previous research work is reported in [6]. The research can be continued by proposed other proportion of sawdust blended in OPC paste.